Measurements of $^{222}$Rn migration in soil - Ioannides, K.G.; Papachristodoulou, C.; Karamanis, D.T.; Stamoulis, K.C.; Mertzimekis, T. J. (J. Radioanal. Nucl. Chem., 1996)
The concentration of radon (222Rn) was measured in the soil near the ground surface, using CR/39 solid state nuclear track detectors. The measurements were carried out in PVC tubes at 0.25 m intervals up to 1.25 m. The detectors were etched in 7N NaOH solutions at 80°C. The ?-tracks from radon's decay were counted using a microscope. A microscopc-camera-computer system developed for automatic counting was also used. The results provide evidence for the non-diffusive transport of radon in soils. A transport length of (46.9 ± 3.2) cm was estimated for radon transport near ground surface. Also the variation of soil's radon concentration was correlate to humidity and atmospheric pressure. Copyright © 1996 Akade?miai Kiado?. All rights reserved.
Keywords: conference paper; drug determination; drug distribution; natural radioactivity; radiochemistry; radon; soil pollution